Pengaruh Lingkungan Kerja, Beban Kerja Dan Etos Kerja Terhadap Kinerja Karyawan Pada Daya Tarik Wisata Tanah Lot - I Gede Putra Astawa; Ni Luh Sili Antari; I Putu Agus Suarsana Ariesta (Universitas Triatma Mulya, 2024)
Improving employee performance at the Tanah Lot Tourist Attraction, work environment, workload and work ethic are things that every company must pay attention to. The purpose of this study is to: 1) ascertain how the workplace environment affects workers' performance at the Tanah Lot Tourist Attraction, 2) Analyze how employee performance is affected by workload at the Tanah Lot Tourist Attraction, 3) Find out how the Tanah Lot Tourist Attraction's employees do in relation to their work ethic, 4) knowing the magnitude of the influence of the work environment, workload and work ethic on the performance of Tanah Lot Tourist Attraction employees. This study employs a quantitative methodology with a 70 employee sample size. Stratified random sampling is the method used in the sampling process. Multiple linear regression analysis, t tests, determination analysis, validity and reliability tests, and classical assumption tests are the analysis approaches that are employed. The research results show Y = 5.646 + 0.233X1 + 0.354X2 + 0.213X3. The study's findings allow for the following conclusions: 1) The work environment has a positive influence on employee performance at the Tanah Lot Tourist Attraction, 2) Work load has a positive influence on employee performance at the Tanah Lot Tourist Attraction, 3) Work ethic has a positive influence on employee performance on Tanah Lot Tourist Attraction, 4) Work environment (X1) and workload (X2) and work ethic (X3) on employee performance (Y) on Tanah Lot Tourist Attraction is 24.3% while the remaining 75.7% is explained by other variables not examined in this research.